Knowledge and attitudes towards rotavirus diarrhea and the vaccine amongst healthcare providers in Yogyakarta Indonesia. Issue 1 (June 2015) - Seale, Holly; Sitaresmi, Mei; Atthobari, Jarir; Heywood, Anita; Kaur, Rajneesh; MacIntyre, Raina; Soenarto, Yati; Padmawati, Retna
Abstract Background Rotavirus has been identified as the most common pathogen associated with severe diarrhoea. Two effective vaccines against the pathogen have been licensed. However, many countries including Indonesia have yet to introduce the vaccine into their national immunisation programs. This study aimed to examine the attitudes of healthcare providers (HCPs) and other health stakeholders towards the pathogen and the vaccine. Methods Semi-structured in-depth interviews were undertaken in two districts of Yogyakarta Province, Indonesia with nurses, midwives, primary care providers, pediatricians and other health stakeholders. Thematic analysis was undertaken. Results Fourteen interviews were conducted between August and October 2013. We identified that while participants do not consider diarrhea to be an important problem in Indonesia, they do acknowledge that it can be serious if not properly treated. While the majority had some level of knowledge about rotavirus, not all participants knew that a vaccine was available. There were mixed feelings towards the need for the vaccine. Some felt that the vaccine is not ranked as a priority as it is not listed on the national program. However, others agreed there is a rationale for its use in Indonesia. The cost of the vaccine (when sold in the private sector) was perceived to be the primary barrier impacting on its use. Conclusions The high cost and the low priority given to this vaccine by the public health authorities are the biggest obstacles impacting on the acceptance of this vaccine in Indonesia. HCPs need to be reminded of the burden of disease associated with rotavirus. In addition, reminding providers about the costs associated with treating severe cases versus the costs associated with prevention may assist with improving the acceptance of HCPs towards the vaccine. Promotion campaigns need to target the range of HCPs involved in the provision of care to infants and pregnant women.